How Hot Are They? Neural Correlates of Genital Arousal: An Infrared Thermographic and Functional Magnetic Resonance Imaging Study of Sexual Arousal in Men and Women. Issue 2 (6th January 2018) - Parada, Mayte; Gérard, Marina; Larcher, Kevin; Dagher, Alain; Binik, Yitzchak M.
Abstract: Background: The few studies that have examined the neural correlates of genital arousal have focused on men and are methodologically hard to compare. Aim: To investigate the neural correlates of peripheral physiologic sexual arousal using identical methodology for men and women. Methods: 2 groups (20 men, 20 women) viewed movie clips (erotic, humor) while genital temperature was continuously measured using infrared thermal imaging. Participants also continuously evaluated changes in their subjective arousal and answered discrete questions about liking the movies and wanting sexual stimulation. Brain activity, indicated by blood oxygen level-dependent (BOLD) response, was measured using functional magnetic resonance imaging. Outcomes: BOLD responses, genital temperature, and subjective sexual arousal. Results: BOLD activity in a number of brain regions was correlated with changes in genital temperature in men and women; however, activation in women appeared to be more extensive than in men, including the anterior and posterior cingulate cortex, right cerebellum, insula, frontal operculum, and paracingulate gyrus. Examination of the strength of the correlation between BOLD response and genital temperature showed that women had a stronger brain-genital relation compared with men in a number of regions. There were no brain regions in men with stronger brain-genital correlations than in women. Clinical Translation: Our findings shed light on the neurophysiologic processes involved in genital arousal for men and women. Further research examining the specific brain regions that mediate our findings is necessary to pave the way for clinical application. Strengths and Limitations: A strength of the study is the use of thermography, which allows for a direct comparison of the neural correlates of genital arousal in men and women. This study has the common limitations of most laboratory-based sexual arousal research, including sampling bias, lack of ecologic validity, and equipment limitations, and those common to neuroimaging research, including BOLD signal interpretation and neuroimaging analysis issues. Conclusions: Our findings provide direct sex comparisons of the neural correlates of genital arousal in men and women and suggest that brain-genital correlations could be stronger in women.